2022
DOI: 10.3390/foods11070976
|View full text |Cite
|
Sign up to set email alerts
|

Proximate, Physicochemical, Techno-Functional and Antioxidant Properties of Three Edible Insect (Gonimbrasia belina, Hermetia illucens and Macrotermes subhylanus) Flours

Abstract: In this study, edible insect flours from Gonimbrasia belina (Mashonzha), Hermetia illucens (black soldier fly larvae) and Macrotermes subhylanus (Madzhulu) were prepared and assessed in terms of proximal, physicochemical, techno-functional and antioxidant properties. The crude protein of the edible insect flours varied between 34.90–52.74%. The crude fat of the insect flours differed significantly (p < 0.05), with H. illucens (27.93%) having the highest crude fat. G. belina was lighter (L*) and yellower (+b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 67 publications
5
14
0
Order By: Relevance
“…These variations could be due to the differences in habitat, climate, sex, processing method and genetic variability [ 26 , 42 , 43 ]. Studies have shown that the protein content of insects ranges between 25 and 75% [ 65 , 66 , 67 , 68 ], which corroborate results of this study. However, it is important to note that the protein values in the current study were significantly higher when compared to some animal and plant protein sources such as milk, beef, roasted goat meat, broiler, pork, eggs, dried whey protein concentrate and soybeans, in which protein constitute between 24 and 45% [ 39 , 69 , 70 ].…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…These variations could be due to the differences in habitat, climate, sex, processing method and genetic variability [ 26 , 42 , 43 ]. Studies have shown that the protein content of insects ranges between 25 and 75% [ 65 , 66 , 67 , 68 ], which corroborate results of this study. However, it is important to note that the protein values in the current study were significantly higher when compared to some animal and plant protein sources such as milk, beef, roasted goat meat, broiler, pork, eggs, dried whey protein concentrate and soybeans, in which protein constitute between 24 and 45% [ 39 , 69 , 70 ].…”
Section: Resultssupporting
confidence: 91%
“…The ash content levels agree with those reported by other authors investigating various edible insects [ 48 , 53 , 68 , 70 , 72 ]. There is a consensus among researchers that ash content of a given sample correlates with its specific mineral elements, which agrees with our findings.…”
Section: Resultssupporting
confidence: 91%
“…The molecular weight distribution of the protein fractions from ultrafiltration and acidic solubilization was determined by sodium dodecyl sulfate–polyacrylamide gel electrophoresis (SDS-PAGE) under reducing conditions [ 22 ]. Samples (10 µL) at a concentration of 2 mg/mL and/or 12 mg/mL were loaded to a 4–20% Mini-PROTEAN ® TGX™ precast gel (Bio-Rad, Hercules, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Bulk density is a major representative property of granules and coarsely ground solids (soil, protein extracts, and gravel) (Mintah et al, 2020). This is an important property of powdered products, due to its significant economic effect on reducing packaging costs (Vanqa et al, 2022). The bulk density results for the protein powder according to the different types of pre-treatments are shown in Figure 2(a).…”
Section: Bulk Density Shear Force and Rehydration Ratiomentioning
confidence: 99%